Biological control agents of cotton pests in Barbados - Colmenárez, Yelitza; Gibbs, Ian H.; Ciomperlik, Matthew; Vásquez, Carlos (ENTOMOTROPICA, 2016)
Cotton, Gossypium barbadense L (Malvaceae) is attacked by different insects, reducing productivity and fibre quality. This study aimed to determine the natural enemies attacking the key cotton pests in Barbados. Seventeen farms were monitored weekly during cotton seasons to determine presence of predators and parasitoids. The monitoring method used was zig-zag evaluating 25 plants in each location. The different stages of the predators presented at the field level were observed and evaluated. Attacked eggs of Lepidoptera and larvae having external parasitoids were collected and isolated to study the endo- and ectoparasitoid species. In addition to the natural enemie’s evaluation, a study was carried out at the field level selecting 10 farmers in order to evaluate the main pest found that leaded to the application of chemical control. Seven predator species and two parasitoid species were found. The most frequent predator species were Chrysoperla sp. (40 %), followed by Cycloneda sanguinea (L). and Allograpta exotica Wiedemann (15 % and 14.5 %, respectively). Parasitoid species found were: Trichogramma chilonis (Ishii) parasitizing Helicoverpa and Heliothis eggs, and Euplectrus sp. as an ectoparasitoid on Alabama argillacea larvae.